Phytocimia Test And Antibacterial Bioactivity Of Extracts from Stem Bark of Artocarpus integer (Thunb.) Merr - Liska Hamzah (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
This research aims to identify the compound group and determine the antibacterial activity of n-hexane, chloroform, and methanol fractions of Artocarpus integer (Thunb.) Merr stem bark. All fractions contain groups of terpenoid and steroid compounds. Antibacterial activity was detemined using agar diffusion method with MHA (Muller Hinton Agar) media on Escherichia coli (gram negative) and Staphylococcus aureus (gram positive). Ciprofloxacin was used as a positive control and methanol as a negative control. The three fractions were able to inhibit the growth of Escherichia coli and Staphylococcus aureus. The chloroform fraction showed the highest activity after 48 hours incubation with inhibition zones of 10.8 and 10.4 mm respectively.